Persepsi dan Partisipasi Anggota Kelompok Tani Hutan (KTH) dalam Pelaksanaan Agroforestri di Areal Kemitraan PT Restorasi Ekosistem Indonesia Provinsi Jambi - Leilea Azizathul Mukhtiya; Marwoto Marwoto; Hamzah Hamzah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The aim of this research is to analyze socio-economic characteristics as well as to analyze people's perceptions and participation as well as the relationship between the two variables. This research is descriptive with a quantitative approach. Analysis of socio-economic characteristics was tested by crosstab test and analysis of perceptions and participation and categorization using a 3 (three) point Likert scale and score interval equations, while analysis of the relationship between perception and participation variables used Spearman's correlation analysis. The results showed that there was a relationship between socio-economic characteristics (age, education, arable area, distance to agroforestry, monthly income, number of family dependents, farming experience, cosmopolitanity) with the perception and participation of KTH members in agroforestry development activities with a value of Approx. The sig of the perception variable is 0.049 and the perception variable is 0.046. The level of perception is in good category with 92.45% good category perception, 5.66% medium category perception, and 5.66% moderate category perception. The level of participation is in the medium category with 32.08% participation in the high category, 37.74% participation in the medium category, and 30.19% participation in the low category. Based on the results of the Spearman's rho correlation test, there is no significant relationship between perceptions and participation of KTH members on agroforestry development, which is 0.071 with a significance of 0.613 (very weak).